2013
DOI: 10.1080/09084282.2012.721149
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Gender Differences on the CNS Vital Signs Computerized Neurocognitive Battery

Abstract: Normative test scores often are corrected for demographic variables that can have an impact on neurocognitive abilities (e.g., gender, age, education, and ethnicity). The purpose of this study is to determine whether there are gender differences on the CNS Vital Signs computerized neurocognitive test battery. Participants, selected from a large normative database, were 100 healthy adults aged 18 to 68 years old (M(age) = 35.8 years, SD = 13.6) with 15.5 years of education (SD = 2.2). Men (n = 50) and women (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
4
9
1
Order By: Relevance
“…In this study, there was no significant gender difference in cognitive function and the response rate. Although this result is consistent with the previous research where cognitive function was measured using CNSVS as in this study [23] and with the preceding study which reported that assessment of the cognitive function of the elderly living at home in the community by MMSE showed no statistically significant gender differences with 24.41±3.62 points for men and 23.64±4.08 for women (p =.171) [5], it is in contrast to results of previous studies that reported that females showed lower cognitive functions than males [3][4][5]. There are gender differences in the mental health of the elderly, and dementia and depression are common risk factors especially for the elderly women [8].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, there was no significant gender difference in cognitive function and the response rate. Although this result is consistent with the previous research where cognitive function was measured using CNSVS as in this study [23] and with the preceding study which reported that assessment of the cognitive function of the elderly living at home in the community by MMSE showed no statistically significant gender differences with 24.41±3.62 points for men and 23.64±4.08 for women (p =.171) [5], it is in contrast to results of previous studies that reported that females showed lower cognitive functions than males [3][4][5]. There are gender differences in the mental health of the elderly, and dementia and depression are common risk factors especially for the elderly women [8].…”
Section: Discussionsupporting
confidence: 94%
“…Men were also significantly faster than women on the SRT task. Sex differences have been shown previously in motor tasks, with men showing faster performance on the FTT (Heaton, 2004; Iverson et al, 2014). Unfortunately, due to the small number of women and especially men in our sample, it is difficult to interpret differential relationships between inflammatory markers and psychomotor performance as a function of sex.…”
Section: Discussionsupporting
confidence: 58%
“…As would be expected, sex did not play a large role, except for the verbal memory domain favoring women, and the psychomotor speed domain favoring men. These findings are consistent with literature on sex differences in performance on other (computerized) tests (Gur et al, 2001;Iverson et al, 2014;Lezak, Howieson, Loring, Hannay, & Fischer, 2004;Silverstein et al, 2007), and reported by Gualtieri (n.d.) who examined sex differences in a subset of participants who completed the CNS VS battery during its standardization study.…”
Section: Discussionsupporting
confidence: 92%